Determination of the energy band-gap of the ceramic ZnO -xTiO₂ using photopyroelectric spectroscopy - Zakaria, Azmi; Rizwan, Zahid; Mohd Ghazali, Mohd Sabri; Shaari, Abdul Halim; Mat Yunus, Wan Mahmood; Hashim, Mansor (Malaysian Solid State Science and Technology Society, 2008)
Photopyroelectric (PPE) spectroscopy is a useful tool for examining optical properties in semiconductor materials. The ceramic (ZnO - xTiO₂) was sintered at 1270⁰C for 1 and 3 hours to investigate the variations of energy band-gap with respect to mol % of dopant TiO₂. The X-ray diffractrometry shows that the crystal structure of ZnO doped at low level remains to be of hexagonal type but has developed second phase, Zn₂TiO₄, at high level. Microstructure and compositional analysis of the selected areas are analyzed using SEM and EDAX. The maximum grain size obtained were 26.8, 52.4 µm at 0.4 mol % of TiO₂ for 1 and 3 hours sintering time, respectively. The band-gap determined from the photopyroelectric spectrum has the value of 2.82 ± 0.01 eV for samples sintered for 1 and 3 hours at the doping level of 0.4 mol % of TiO₂ and decreases with the increase of TiO₂.